Extravehicular Electron Measurement Based on an Intravehicular Pixel Detector. Issue 11 (20th November 2019) - Kroupa, M.; Campbell‐Ricketts, T.; Bahadori, A. A.; Pal Chowdhury, R.; Empl, A.; George, S. P.; O'Brien, T. P.
Abstract: We demonstrate indirect measurement of the electron flux outside space vehicles designed to carry crew, using a pixel detector situated inside the space craft. While the vehicle walls shield the detector from directly seeing the electrons, we show that bremsstrahlung generated in the shielding is visible and furthermore that fluorescence induced by this bremsstrahlung in components of the detector generates a sharply peaked characteristic signature. We show that measurements from the Exploration Test Flight 1 of the Orion Multi‐Purpose Crew Vehicle and from the International Space Station correlate very well with AE9‐based modeled electron flux predictions and with measurements from other instruments on the International Space Station and on the Polar Operational Environmental Satellites. We also present detailed Monte Carlo simulations performed with FLUKA, confirming the mechanism generating our electron signal. Key Points: Indirect measurement of the electron flux outside space vehicles designed to carry crew